Human factors and ergonomics to improve performance in intensive care units during the COVID-19 pandemic - Della Torre, Valentina; Nacul, Flavio; Rosseel, Peter; Baid, Heather; Bhowmick, Kaushik; Szawarski, Piotr; K. Sahoo, Tapas; Utku, Tughan; Wong, Adrian; L.N.G. Malbrain, Manu (Anestezjologia Intensywna Terapia, 2021)
The COVID-19 pandemic has tested the very elements of human factors and ergonomics (HFE) to their maximum. HFE is an established scientific discipline that studies the interrelationship between humans, equipment, and the work environment. HFE includes situation awareness, decision making, communication, team working, leadership, managing stress, and coping with fatigue, empathy, and resilience. The main objective of HF is to optimise the interaction of humans with their work environment and technical equipment in order to maximise patient safety and efficiency of care. This paper reviews the importance of HFE in helping intensivists and all the multidisciplinary ICU teams to deliver high-quality care to patients in crisis situations.